Functional Characterization of Lycopene β- and ε-Cyclases from a Lutein-Enriched Green Microalga Chlorella sorokiniana FZU60 - Hong Fang; Junjie Liu; Ruijuan Ma; Yiping Zou; Shih-Hsin Ho; Jianfeng Chen; Youping Xie (Marine Drugs, 2023)
Lutein is a high-value carotenoid with many human health benefits. Lycopene β- and ε-cyclases (LCYB and LCYE, respectively) catalyze the cyclization of lycopene into distinct downstream branches, one of which is the lutein biosynthesis pathway, via α-carotene. Hence, LCYB and LCYE are key enzymes in lutein biosynthesis. In this study, the coding genes of two lycopene cyclases (CsLCYB and CsLCYE) of a lutein-enriched marine green microalga, Chlorella sorokiniana FZU60, were isolated and identified. A sequence analysis and computational modeling of CsLCYB and CsLCYE were performed using bioinformatics to identify the key structural domains. Further, a phylogenetic analysis revealed that CsLCYB and CsLCYE were homogeneous to the proteins of other green microalgae. Subcellular localization tests in Nicotiana benthamiana showed that CsLCYB and CsLCYE localized in chloroplasts. A pigment complementation assay in Escherichia coli revealed that CsLCYB could efficiently β-cyclize both ends of lycopene to produce β-carotene. On the other hand, CsLCYE possessed a strong ε-monocyclase activity for the production of δ-carotene and a weak ε-bicyclic activity for the production of ε-carotene. In addition, CsLCYE was able to catalyze lycopene into β-monocyclic γ-carotene and ultimately produced α-carotene with a β-ring and an ε-ring via γ-carotene or δ-carotene. Moreover, the co-expression of CsLCYB and CsLCYE in E. coli revealed that α-carotene was a major product, which might lead to the production of a high level of lutein in C. sorokiniana FZU60. The findings provide a theoretical foundation for performing metabolic engineering to improve lutein biosynthesis and accumulation in C. sorokiniana FZU60.